Knowledge Management Practices in the Public University Libraries: Librarian's Perspective - Roslina Othman; SK Mamun Mostofa (Universitas Pendidikan Ganesha, 2022)
Some libraries play an essential role in teaching and learning but there are some constraints. It causes universities to be able to identify various factors and overcome the challenges of implementing KM in libraries. This study aims to explore current Knowledge Management (KM) practices in Public University Libraries (PUL). This type of research is qualitative. The methods used in collecting qualitative data are observation, interviews, and questionnaires. The instrument used is the interview sheet. The sample of this research is 11 people using purposive sampling. The collected data were analyzed using content analysis. The findings reveal no formal KM program in any of the selected universities. This study found that a prudent strategy for KM implementation, recruiting skilled personnel, ongoing training programs for staff and users, leadership, ICT infrastructure, higher authority decisions, budgets, and lack of qualified personnel are critical success factors for KM implementation in PUL. This research identified many challenges that PUL usually faces in their efforts to implement KM: lack of budget, lack of user awareness, lack of trained staff, and outdated technology.